Can AI create better lesson plans than humans? This is what Malaysian english instructors think - Wan Noor Farah, Wan Shamsuddin; Nur Amalina, Mohd Shariff (UPM, 2024)
The advent of ChatGPT sparks great debate amongst educators as some may view this as a new advancement in technology, whilst some are apprehensive on its usage in language classrooms. This study seeks to investigate the perceptions of Malaysian English instructors in using ChatGPT to create lesson plans. Lesson plans are developed to offer teachers a broad framework for structuring their lessons, typically created by teachers in alignment with the syllabus set by the national curriculum. An online survey was administered to English instructors to inquire about their experience and attitude towards using ChatGPT in creating lesson plans. This is then followed by a semistructured interview with several instructors for more qualitative findings. The results indicated that Malaysian English teachers have a positive outlook towards using the technology especially when designing lesson plans. The advantages of using ChatGPT when doing lesson plans include time-efficient, high success rate and creative lessons.